The Role of The Marketing Mix On Student Decisions In Choosing A College - Effendi, Oci; Hardilawati, Wan Laura; Setianingsih, Rahayu (International Journal of Indonesian Business Review, 2022)
Purpose –The purpose of this study was to determine the effect of the marketing mix on the decisions of new students in choosing a college at the University of Muhammadiyah Riau. The sampling method used is the probability sampling method. In this study, the sampling technique used is simple random sampling. The analytical technique used in this research is data analysis with the help of the SPSS (Statistical Product And Service Solution) application program. Methodology/approach –Using quantitative analysis, it has a population of 2,325 people by sampling 200 people. Findings –The results of the analysis obtained from hypothesis testing are that product, promotion, place, process have a positive but not significant effect on the decision to choose new students at the Muhammadiyah University of Riau. While people and physical evidence have a positive and significant effect on the decision to choose new students at the Muhammadiyah University of Riau. And for the price has a negative but not significant effect on the decision to choose new students at the University of Muhammadiyah Riau. Novelty/value –The dependent variables used are product, price, promotion, place, people, process and physical evidence.